Positive or Negative Freedom? Types of Freedom Towards EU COVID-19 Certificates in Poland. A Pilot Study - Gruchoła, Małgorzata; Sławek-Czochra, Małgorzata; Dyczewski, Błażej (Roczniki Filozoficzne, 2025)
The aim of this paper was to explore the relationship between the respondent’s identified type of freedom and their attitudes towards the potential decision to introduce EU COVID-19 certificates. We take the COVID-19 certificate assessments as a context for analysing the practical functioning of different types of freedom in crisis situations. A further aim is to structure attitudes towards the certificates by superimposing a grid composed of theoretical types of freedom (positive freedom and negative freedom, and ‘from’ and ‘to’ freedom). Four types of freedom were the subject of the empirical research: freedom of choice, freedom as autonomy, freedom as self-realisation and freedom as a human right used to establish the dominant type of freedom (positive freedom - negative freedom; freedom ‘from’ - freedom ‘to’) in the face of the possibility of COVID-19 certificates.